El derecho constitucional a vivir en un ambiente sano: Radiografía del manejo de los recursos naturales en el gobierno de Rafael Correa - Morales Naranjo, Viviana (2021)
The Ecuadorian Constitution recognizes “the right of the population to live in a healthy and ecologically balanced environment, which guarantees sustainability and good living.” Since the bill of this right, Ecuador develops a series of laws and public policies, in order to effectively fulfill this right. The political program of the ex-President of the Republic of Ecuador, Rafael Correa, focused on the use of renewable and non-renewable resources, putting forward the need to reduce poverty and redistribute wealth. This research analyzes the law and public policies about exploitation of natural resources, executed during 2007-2017 period. It will also be treated to answer the following question: The legal and political measures were in detriment of environmental protection? or, in an opposite way, Rafael Correa’s government was able to achieve a social-economic-environmental balance and the consequent effectiveness of the right to live in a healthy environment?